Förflytta grisar (Sus scrofa domesticus) - Toivonen, Tina (2020)
In Sweden 2.65 million pigs (Sus scrofa domesticus) were slaughtered in 2018, whilst the number throughout Europe was startling 255 million heads in 2017. Moving and handling of pigs is one of the most stressful events in a pig’s life and is carried out with more or less aversive methods that may stress the pigs to varying degrees. The purpose of this study was to investigate if it was possible to move and handle the pigs in a less aversive way whilst retaining the same time and effort level. 120 pigs were used of which 60 were trained in groups of 10 individuals at a time, at the research centre of Lövsta. The training method applied was positive reinforcement where a clicker and a novel object consisting of a target stick were used for three sessions per group. Finally, the pigs from each of the twelve pens were moved to simulate moving at time of slaughter, from the home pen to a new pen using two different methods; control or trained. Six of the twelve groups constituted the control group and were moved conventionally from behind using a moving board, whilst the other six groups that had been previously trained to follow a target were moved and handled through this method. The trained group was significantly slower in being moved to the new pen, probably due to their strong inherent need to explore novel environments. The pigs who were conventionally moved did not have the opportunity to explore the novel environment as they were rushing to get away from the handler. Signs of stress such as barking were equal in both control group and trained group although these findings could be debated as originating from different emotions in the pigs. The movement of the pigs back to their home pens was significantly quicker in both the trained and the untrained groups compared to the initial moving, showing that habituation to a novel environment occurs rapidly.